Feature conditioned resolution of hiatus in Chichewa - Sabao, Collen (Taylor & Francis, 2016)
This article examines the morphophonological environments in which vowel sequences occur in Chichewa and explains the synchronic hiatus resolution strategies that are employed in this language to remove these dispreferred vowel cluster configurations. This investigation demonstrates that the major motivation for resolving hiatal configurations in Chichewa, like in many other Bantu languages, is to maintain the preferred canonical consonant-vowel (CV) syllable structure. The analysis of data used in this study is mainly couched within the theoretical explica-tions of Optimality Theory (OT) as enunciated by Prince and Smolensky (1991, 1993), McCarthy and Prince (1999), Archaengeli and Langendoen (1997), and Kager (1999); Distinctive Feature Theory as discussed by Chomsky and Halle (1968) as well as the generative CV-phonology model of syllable structure as discussed by Clements and Keyser (1983). This article argues for vowel-feature sensitive repair of hiatal configuration in Chichewa. Observing such a vowel-feature sensitive based repair of hiatal configuration analysis, which this article argues to be largely ONSET motivated/triggered and the featural properties of the phonological structures of the language under study, the language’s reactions to such dispreferred vowel clusters and its phonotactics are here examined. Repair strategies for such hiatus configurations are discussed, including glide formation, consonantal and/or glide insertions, vowel deletion and coalescence. The analysis adopted here implies that the resolution hiatus arises from incompatibilities in the features of the vowels straddling a word boundary. It argues that these repair strategies are largely motivated by language internal constraint ranking systems which in many Bantu languages seem to largely prefer the preservation of [−] features over [+] features, i.e. the ranking [−F’]≫[+F’]